Pharmacognostic and Phytochemical Profile of Karavira (Nerium indicum Mill.) Roots with Reference to its Change after Shodhana (Purification Process as per Classics) - Veerappa Hugar; Daneshwari S Kanashetti; Kamal Nayan Dwivedi (Pharmacognosy Research, 2023)
Background: Standardization is a crucial method for establishing the identification, purity, safety, and quality of herbal medicines. Numerous morphological, physicochemical, and phytochemical investigations are performed in order to standardize a medication. For the purpose of establishing standards for unprocessed crude drug, the quantitative assessment of some phytochemical characteristics is necessary. Objectives: The current work discusses the standardization of Nerium indicum root based on several pharmacognostic characteristics, and the identification of these traits will help subsequent researchers to study this species pharmacology. Materials and Methods: Sectioning of fresh root sample of N. indicum, assessment of macroscopic, microscopic, and physicochemical parameters were done based on standard procedures as per API and WHO. Qualitative phytochemical screening, quantitative estimation of total polyphenolic content and cardiac glycoside content of ashodhita (non-purified) and shodhita (purified) hydroalcoholic extract were carried out through standard procedures. Observation and Results: Pharmacognostic analysis confirms the identity of genuine root sample of Nerium indicum. Phytochemical analysis of Ashodhita and Shodhita hydroalcoholic extract shows presence of Carbohydrate, Alkaloids, Flavonoids and Saponins and negative test for Tannins, Starch and Steroids. Quantitative estimation of total phenolic content was found to be is 4.14% w/w and 2.59% w/w of pre and post shodhita extract respectively. Total cardiac glycoside content was found to be 3.27% w/w and 3.05% w/w in Ashodhita and Shodhita extract respectively. Conclusion: The results of the current investigation indicate that the physico-chemical and phytochemical analyses of Nerium indicum root, produced a set of qualitative and quantitative pharmaco-botanical parameters that can be used as a valuable source of data to establish the identity and to assess the quality and purity of the plant material in subsequent studies.
Keywords: Karavira; Nerium indicum; Phytochemical study.; Shodhita and Ashodhita Karavira